Water is the vessel through which we ride the waves of changing climates - Zimmermann, Karl; Sancho, Camila; Kumaran, Varshaa; Kalam, Sifat (Frontiers in Water, 2024)
Acting through water, climate change may affect livelihoods, societal structures, and political conflicts, hindering progress toward poverty reduction. Expanding on themes from the WEST Water Conference, this perspective paper considers how water insecurity from changing climates has unequal impacts within societies, water and gender roles, changing livelihoods, and shifting cultural norms. Opportunities are shared to build resilience into our future water systems. First, technologies are considered for tracking water availability, quality, and usage. Second, collaborating with nature to manage water builds into the idea of blue-green cities. And third, the route to community participation in managing resilient water systems is with an empowered population, made possible through a three-step process of Awareness, Education, and Resources.